The Influence of Financial Technology on MSME Business Performance: Mediation of Financial Literacy, Entrepreneurial Orientation, and Government Policy as a Moderator - Fadali Rahman; Ismi Fitri Aulia; Zef Risal (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Micro and Small Enterprises (MSEs) play a strategic role in the national economy, but they still face various challenges in improving their business performance, particularly in the digital era. This study aims to analyze the influence of financial technology on MSE business performance by considering the mediating role of financial literacy and entrepreneurial orientation, as well as the moderating role of government policy. This study uses a quantitative approach with a survey method of MSE actors. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with a total of 196 respondents from MSEs who implement digital payments, e-wallets, QRIS, or digital financing platforms. The results of the study indicate that financial technology has a positive effect on financial literacy, entrepreneurial orientation, and MSE business performance. Furthermore, financial literacy and entrepreneurial orientation are proven to act as mediating variables in the relationship between financial technology and MSE business performance, with entrepreneurial orientation having a more dominant influence. These findings indicate that the adoption of financial technology will have a more optimal impact when accompanied by an innovative and proactive entrepreneurial attitude. Meanwhile, government policies have not been able to play a strong role as a moderating variable in strengthening the influence of financial literacy on MSE business performance, indicating the need for more effective and implementable policies. Overall, this study emphasizes the importance of integrating the use of financial technology, increasing entrepreneurial capacity, and strengthening financial literacy in efforts to improve the performance and sustainability of MSEs in the digital era.